Pharmacology and therapeutics of asthma and COPD - Barnes, Peter J., 1946-; Page, C. P. (Springer, 2017)
"The present volume is supposed to be a major reference resource for chest physicians and those involved in the development of novel pharmaceutical entities for these diseases. Internationally recognized authorities review the most important new information on the advances in our understanding of the pathogenesis and treatment of these diseases, including the substantial advances in the topical delivery of inhaled medicines. Each chapter is extensively referenced, generously illustrated with clear diagrams and photographs, and represents a state-of-the-art review of this important area of respiratory medicine"--Publisher's description.
Revision of: Pharmacology and therapeutics of asthma and COPD / editors, Clive P. Page and Peter J. Barnes. ©2004.
Keywords: Asthma -- Chemotherapy.; Lungs -- Diseases, Obstructive -- Chemotherapy.; Antiasthmatic agents.; elektronické knihy; electronic books